(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Urinary tract infection (UTIs) are considered to be the most common infections in humans.Aims: this study aimed to evaluate the immune status of the patients with UTI by studying of (IL-6 and IL-10).Subjects and Methods: A total of 49 UTI patients infected with gram –ve bacteria and 25 healthy controls were enrolled in this study. Urine samples from UTI cases was collected in AL-Imam AL-Hussain teaching hospital in Thi- Qar province, during the period from February 2014 to July 2014. Urinary isolates were identified by conventional methods.3 ml were collected in plastic tube and then centrifuged at 3000 round per minute (rpm) for 5 min to obtain sera. And after the serum sample were collected they were divided into two apendroff tubes and stored in deep freeze at – 20º C until performing IL-6 and IL-10. (Lewis et al., 2006).Results: Patients with E. coli infection accounted for 26 (53.06%); other culture results were as follows: 7 (14.29 %) patients had K. pneumonia, 9 (18.37%) patients had P. aerogenosa, 4 (8.16%) had Proteus and 3 (6.12%) patients had K.oxytoca. Measure levels of serum IL-6 and IL-10 for study group against control group, which is showed a significant increase (P ≤ 0.01) in the levels of interleukins (IL-6, IL-10) in all serum patients compared to the control group.Conclusion: E- coli was most common causative agent in UTI, The high rate concentration of IL-6 and IL-10 in patients with UTI compared with the healthy control group. This refers to the injury for their role in the immune response.